[Cu(NHC)]‐Catalyzed C−H Allylation and Alkenylation of both Electron‐Deficient and Electron‐Rich (Hetero)arenes with Allyl Halides. Issue 5 (22nd December 2015) - Xie, Weilong; Chang, Sukbok
Abstract: New reactivity of a [Cu(NHC)] (NHC=N‐heterocyclic carbene) catalyst is disclosed for the efficient C−H allylation of polyfluoroarenes using allyl halides in benzene at room temperature. The same catalyst system also promotes an isomerization‐induced alkenylation of initially the generated allyl arenes when the reaction is run in tetrahydrofuran. Significantly, not only electron‐deficient but also electron‐rich (hetero)arenes undergo this double‐bond migration process, thus leading to alkenylated products. The present system features mild reaction conditions, broad scope with respect to the arene substrates and allyl halide reactants, good functional‐group tolerance, and high stereoselectivity. Abstract : Something new for Cu : New reactivity of a [Cu(NHC)] (NHC=N‐heterocyclic carbene) catalyst is disclosed for the direct C−H allylation and alkenylation of both electron‐deficient polyfluoroarenes and electron‐rich heteroarenes. This catalyst system leads to mild reaction conditions, broad scope with respect to the arenes and allyl halides, good functional‐group tolerance, and high stereoselectivity.